Testing Baron and Kenny’s Preliminary Conditions for Mediating or Moderating Variables in Structural Equation Modeling - Fiedler, Beth Ann; Sivo, Stephen A. (Advances in Social Sciences Research Journal, 2015)
A common misnomer in statistical analysis is the identification of intervening variables as either moderating or mediating as a result of placement of another latent construct or variables between exogenous and endogenous variables in a Structural Equation Model (SEM). However, placement does not determine variable status. Determination of variable status requires the application of Baron and Kenny’s preliminary conditions and analysis for determining whether a variable is moderating, mediating, or in fact, intervening. This procedure aids in statistically representing the actual strength and direction of variables in order to improve reporting predictor results on outcomes. An SEM was developed using the results of the analysis of the Biomedical Engineering Interdepartmental (BEI) Survey conducted in 2011. This document illustrates the application of Baron and Kenny’s method to the BEI survey SEM model.